Neural substrates of impulsive decision making modulated by modafinil in alcohol-dependent patients. Issue 13 (5th March 2014) - Schmaal, L.; Goudriaan, A. E.; Joos, L.; Dom, G.; Pattij, T.; van den Brink, W.; Veltman, D. J.
Abstract : Background: Impulsive decision making is a hallmark of frequently occurring addiction disorders including alcohol dependence (AD). Therefore, ameliorating impulsive decision making is a promising target for the treatment of AD. Previous studies have shown that modafinil enhances cognitive control functions in various psychiatric disorders. However, the effects of modafinil on delay discounting and its underlying neural correlates have not been investigated as yet. The aim of the current study was to investigate the effects of modafinil on neural correlates of impulsive decision making in abstinent AD patients and healthy control (HC) subjects. Method: A randomized, double-blind, placebo-controlled, within-subjects cross-over study using functional magnetic resonance imaging (fMRI) was conducted in 14 AD patients and 16 HC subjects. All subjects participated in two fMRI sessions in which they either received a single dose of placebo or 200 mg of modafinil 2 h before the session. During fMRI, subjects completed a delay-discounting task to measure impulsive decision making. Results: Modafinil improved impulsive decision making in AD pateints, which was accompanied by enhanced recruitment of frontoparietal regions and reduced activation of the ventromedial prefrontal cortex. Moreover, modafinil-induced enhancement of functional connectivity between the superior frontal gyrus and ventral striatum was specifically associated with improvement in impulsive decision making. Conclusions: These findings indicate that modafinil can improve impulsive decision making in AD patients through an enhanced coupling of prefrontal control regions and brain regions coding the subjective value of rewards. Therefore, the current study supports the implementation of modafinil in future clinical trials for AD.